404: file not found web archives and the challenges of preserving digital film promotion. - Walden, Kim Louise (Historical Journal of Film, Radio & Television, 2023)
This article builds upon the invitation at the end of a previous contribution to the Historical Journal of Film, Radio and Television by Keith Johnston to take up the methodological challenges relating to the study of historical promotional materials. The article focuses on a form of promotion that has emerged with the advent of the Internet – the film website. It starts with an examination of the archival record online. It considers the development of web archiving and the nature of the archive as it transforms from the physical to the digital. In the light of this history a selection of film promotion repositories is examined: the largest online archive in the world- the Internet Archive; a German museum initiative - DigitalCraft.Org; new kinds of archives like the Webby Awards and an enthusiast's blog – Movie Marketing Madness. Through an investigation of these online archives, the contours of this promotional form emerge and the mapping of its historical development can commerce.